Development of an integrated system of sensors for organoleptic characterization of pisco - Calzado, Joan (2010)
We have built an integrated system of sensors for organoleptic characterization of a liquor distilled from grapes called pisco analyzing its liquid phase in an electrochemical cell, in addition is analyzed its gas phase in a small chamber with the gas sensors. We have designed an electronic nose with 4 gas sensor with different characteristics (Figaro Inc.) and an electronic tongue based on an electrochemical cell with two electrodes of stainless steel with Pt and Au, respectively. The system is composed mainly of gas sensors, actuators valves, liquid and gas pumps that are governed by the P1C18F4523 microcontroller which also are responsible for sending data to the computer. The prototype developed is robust, economical and portable. For data processing we have developed a program in Matalab using principal components analysis. We have tested with different piscos obtaining interesting fingerprints of the pisco.